Adolescents’ Developing Sensitivity to Orthographic and Semantic Cues During Visual Search for Words - Vibert, Nicolas; Braasch, Jason L. G.; Darles, Daniel; Potocki, Anna; Ros, Christine; Jaafari, Nematollah; Rouet, Jean-François (Frontiers in Psychology, 2019)
Two eye-tracking experiments were conducted to assess the influence of words either looking like the target word (orthographic distractors) or semantically related to the target word (semantic distractors) on visual search for words within lists by adolescents of 11, 13 and 15 years of age. In Experiment 1 (literal search task), participants saw the target word before the search (e.g., “raven”), whereas in Experiment 2 (categorical task) the target word was only defined by its semantic category (e.g. “bird”). In both experiments, participants’ search times decreased from fifth to ninth grade, both because older adolescents gazed less often at non-target words during the search and because they could reject non-target words more quickly once they were fixated. Progress in visual search efficiency was associated with a large increase in word identification skills, which were a strong determinant of average gaze durations and search times for the categorical task, but much less for the literal task. In the literal task, the presence of orthographic or semantic distractors in the list increased search times for all age groups. In the categorical task, the impact of semantic distractor words was stronger than in the literal task because participants needed to gaze at the semantic distractors longer than at the other words before rejecting them. Altogether, the data support the assumption that the progressive automation of word decoding up until the age of 12 and the better quality of older adolescents’ lexical representations facilitate a flexible use of both the perceptual and semantic features of words for top-down guidance within the displays. In particular, older adolescents were better prepared to aim at or reject words without gazing at them directly. Finally, the overall similar progression of the maturation of single word visual search processes and that of more real-life information search within complex verbal documents suggests that the young adolescents’ difficulties in searching the Web effectively could be due to their insufficiently developed lexical representations and word decoding abilities.